EFECTO DE TRES ANTIBIOTICOS SOBRE LOS PARÁMETROS PRODUCTIVOS EN POLLOS DE LÍNEA COBB 500 - Vilca Quiñones, Idira Stephanie (2017)
This research was developed in the experimental center of the company Agroindustrias Florida S.A.C., located in the district of Huanchaco, province of Trujillo, department of La Libertad; during the months of February to April 2016, to determine the effect of the inclusion of the antibiotics Neomicina and Amoxicillin on the diet on the production parameters of the Cobb 500 chickens. We used 270 chickens, with a completely random design, distributed in Three treatments: T0 without antibiotics, T1 with Neomycin 150 ppm + Amoxicillin 150 ppm + Monensina 100 ppm, supplied from day 4 to 14 days of age, T2 with Neomycin 150 ppm + Amoxicillin 150 ppm + Monensina 100 ppm, delivered from day 1 to 14 days of age. The three treatments were challenged the first day with a mixture of E. coli and Staphylococcus sp., Inoculating 150 ppm each, 1 ml was given for each baby chicken. In the final weight parameter T2 was higher with 2,45 kg T1 was 2,43 kg and T0 was 2,18 kg. Highly significant differences were calculated (p<0,01). For weight gain T2 was higher with 2,41 kg, T1 had 2,39 kg and T0 with 2,14 kg. Highly significant statistical differences (p<0,01) were calculated. Food intake was higher in T0 with 4,09 kg, T2 was 4,07 kg and T1 with 4,01 kg. No statistically significant differences were calculated (p>0,05). The best feed conversion was for T2 with 1.59; The T1 was 1,65 and the T0 was 1,81. Significant statistical differences were calculated (p<0,05). The mortality rate was higher in T0 with 18,8%, T1 with 4,4% and T2 with 2,2%. Highly significant statistical differences were found (p<0,01).